1993
DOI: 10.1159/000217850
|View full text |Cite
|
Sign up to set email alerts
|

Expansion of Peripheral Blood Natural Killer Cells Correlates with Clinical Outcome in Cancer Patients Receiving Recombinant Subcutaneous lnterleukin-2 and Interferon-α-2

Abstract: Natural killer (NK) cells are believed to contribute to the clinical efficacy of cancer immunotherapy using recombinant interleukin-2 (rIL·2) in humans. In previous trials of high-dose i.v. rIL-2, however, no correlation has been established between circulating NK cells and treatment response. Between January 1989 and October 1990, we treated a total of 47 outpatients with advanced tumors using low-dose s.c. rIL·2 and interferon-α-2 (rIFN-α). Therapy consisted of a 2-day rIL·2 pulse at 18 million IU/m2/ day, f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
20
1

Year Published

1996
1996
2015
2015

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(21 citation statements)
references
References 12 publications
0
20
1
Order By: Relevance
“…Eosinophil numbers correlated positively with response in a study by Atzpodien et al (1991), who treated RCC patients in accordance with a 7-week protocol of S.C. JFNa and low-dose IL-2. The same authors reported that at completion of that treatment, absolute numbers of CD56+ lymphocytes were higher in responders than in non-responders (Atzpodien et al, 1993). Differences in serial lymphocyte (sub-set) or eosinophil counts between responders and non-responders in our study were non-significant at most time points studied.…”
Section: Discussioncontrasting
confidence: 51%
“…Eosinophil numbers correlated positively with response in a study by Atzpodien et al (1991), who treated RCC patients in accordance with a 7-week protocol of S.C. JFNa and low-dose IL-2. The same authors reported that at completion of that treatment, absolute numbers of CD56+ lymphocytes were higher in responders than in non-responders (Atzpodien et al, 1993). Differences in serial lymphocyte (sub-set) or eosinophil counts between responders and non-responders in our study were non-significant at most time points studied.…”
Section: Discussioncontrasting
confidence: 51%
“…It has also been shown that tumor necrosis factor, an agent used in failed attempts at immunotherapy, stimulates T-cell and not NK cell activity [10]. Moreover, expansion of NK cell populations correlates with improved outcomes in patients receiving immunotherapy [6]. NK cells, in fact, are the first cells of the tumor response to secrete tumor necrosis factor and interferon-γ, which, in turn, stimulates type 1 helper T-cell (Th1) differentiation [22], which may account for the recruitment of CTL to regressing lesions.…”
Section: Discussionmentioning
confidence: 99%
“…A small number of melanomas spontaneously regress, which is a process accompanied by a host response represented by tumor-associated lymphocytes (TALs), pigment incontinence, neovascularization, and fibrosis; however, no effecter mechanism has been identified for this native phenomenon [5]. Studies have shown that cytotoxic cells such as cytotoxic T-lymphocytes (CTLs) and natural killer (NK) cells are likely mediators [5,6]. CTLs are identified by expression of the CD8 antibody, and NK cells express CD56.…”
Section: Introductionmentioning
confidence: 99%
“…Although this moderate dose and schedule of IL-2 and IFN has not been formally studied in melanoma, the tolerability and activity of this regimen in renal cell cancer made it reasonable to see whether there was enhanced activity when combined with chemotherapy, provided this was done in the context of a randomized study. The dose of IL-2 used was based on experience of the immunological changes that occur with IL-2 given subcutaneously, using a schedule that was previously well tolerated (Atzpodien et al, 1993;Castello et al, 1993). Similarly, the dose of interferon has been used in a number of interferon-DTIC studies (Falkson et al, 1991).…”
mentioning
confidence: 99%